Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/gea.21714
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Hellenistic to nomadic cultural patterns through pottery in ancient Termez, Uzbekistan

Abstract: We present the archaeological contextualization and the archaeometric characterization of slipped and nonslipped tableware and common wares from Termez in south Uzbekistan. The aims are, first, to evaluate the manufacture of pottery in the city and region (ancient Bactria) after the conquest of Alexander the Great in the late 4th century B.C. so as to detect Hellenistic Mediterranean influences, and, second, to investigate the evolution in pottery manufacturing following the arrival of the Yuezhi nomadic tribe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…Even if some chemical differences have been detected among the vessels classified in groups A and B, all of them have been considered as local products. They consist of calcareous pastes (CaO: 10-11 wt%) with similar chemical composition to the local productions from Termez related to the pre-Islamic period (Tsantini et al, 2016;Martínez Ferreras et al, 2019b). Indeed, the mineralogical and petrographic composition of these vessels is consistent with the local raw materials (clayey sediments) also analysed from Termez and with the geological composition of the region.…”
Section: Methodssupporting
confidence: 62%
“…Even if some chemical differences have been detected among the vessels classified in groups A and B, all of them have been considered as local products. They consist of calcareous pastes (CaO: 10-11 wt%) with similar chemical composition to the local productions from Termez related to the pre-Islamic period (Tsantini et al, 2016;Martínez Ferreras et al, 2019b). Indeed, the mineralogical and petrographic composition of these vessels is consistent with the local raw materials (clayey sediments) also analysed from Termez and with the geological composition of the region.…”
Section: Methodssupporting
confidence: 62%
“…Moreover, the compositional differences detected among these samples and those found at Kampyr Tepe and Termez reveal that they were not produced in the Amu Darya floodplain. At Termez, all the samples analyzed were recovered from the alluvial plain (sectors AC1 and AC2) and have been considered as local/regional products (Martínez Ferreras et al., 2019). In contrast, for the tableware from the Tchingiz Tepe, dated to the Kushan and Kushano‐Sasanian periods, a local provenance has been established (Gurt Esparraguera et al., 2015).…”
Section: Archeological Contextsmentioning
confidence: 99%
“…The chemical, mineralogical, and petrographic composition of the studied collection was characterized in previous studies (Gurt Esparraguera et al., 2015; Martínez Ferreras et al., 2016, 2019) by using an ensemble of archeometric techniques, including Wavelength Dispersive X‐Ray Fluorescence, X‐Ray Diffraction, Scanning Electron Microscope with Energy Dispersive X‐Ray Spectroscopy, and thin section optical microscopy. These studies prove that the chemical variability is very low between the ceramic vessels found in the same site, suggesting the use of very similar raw materials and therefore, a common local/regional origin.…”
Section: Archeological Contextsmentioning
confidence: 99%
See 2 more Smart Citations